A Case of Rapidly Progressing Granulomatous Myocarditis: What Is the Diagnosis?. (8th March 2021) - Cao, Jessica; Schwartz, Yosef Y.; Lomasney, Jon W.; Narang, Akhil; Okwuosa, Ike S.; Avery, Ryan; Passman, Rod S.; Cooper, Leslie T.; Vorovich, Esther
Abstract : Supplemental Digital Content is available in the text.